Water lifting devices - Fraenkel, P.L. (FAO RomeIT, 1986)
Provides a basis for comparing and choosing between all present and (near) future options for lifting irrigation water on small and medium sized land-holdings. Supplies information on techniques for lifting water for purposes other than irrigation.